Koperasi Sebagai Harapan Perekonomian Masa Depan - Hendragunawan S. Thayf; Supartiningsih Supartiningsih; M. Mukhtasar Syamsuddin (Coopetition : Jurnal Ilmiah Manajemen, 2022)
Corporations as one of the important engines of modern capitalism have been able to create abundant wealth in the economy. However, along with its success, social life and the natural environment are in a precarious condition. This welfare machine actually threatens justice and sustainability, two values that are no less important than wealth, for human existence. Therefore, the authors then propose cooperatives as an institutional alternative. By reviewing history and using empirical data, it can be seen that although in other developed economies, cooperatives can play a significant role, in Indonesian, our cooperatives only play a minor role. Therefore, the authors propose the concept of a generic cooperative as an effort to represent the original and basic cooperative spirit.